“Prey to some cureless disquiet”: Polidori’s Queer Vampyre at the Margins of Romanticism - Rigby, Mair (Romanticism on the Net, 2004)
AbstractDr. John Polidori’s appropriative rewriting of Lord Byron’s unfinished “Fragment” as The Vampyre has long been of interest to the field of Gothic studies for its representation of the first coherent vampire in English Literature. In recent years, the inscription of sexual rhetoric in both texts has attracted further critical attention. Featuring men who traverse the explosively tense line between compulsory homosocial relations and the culturally prohibited horrors of homoerotic desire, these texts can certainly be read in the light of Eve Kosofsky Sedgwick’s identification of the homophobic “paranoid gothic.” However, considered together, The Vampyre and the “Fragment” reveal more than anxieties about male bonding. In this essay, I explore the nexus of concerns raised by The Vampyre, its relation to the “Fragment,” and the perceived relationship between Polidori and Byron with the aim of working towards a repositioning of these marginal Gothic works as indeed both disquieting and deeply queer. The “Fragment” represents Byron’s contribution to the now mythical “ghost story competition” at Villa Diodati in 1816 which also inspired the writing of Frankenstein. The man Mary Shelley dubbed “Poor Polidori” stands on the margins of this famous gathering, but he and his story remain a haunting presence in more than one respect. Focussing upon the way in which modern sexual discourse has helped make the author into an object of sexual interest, I propose that the production of Polidori as a strange, sexually suspect figure strikingly illustrates how the Gothic rhetoric of the sexual “unspeakable” can reverberate out from the text and into our thinking about the author.